Risk Assessment and Mitigation Strategy of Hybrid Energy Storage System in 11-m Fully-Electric Seabus - Hisyam Amru Osamah; Agoes Santoso; Nurhadi Siswantoro (International Journal of Marine Engineering Innovation and Research, 2026)
Risk assessment of Energy Storage Systems (ESS) in ships is a fundamental requirement to ensure operational safety in the maritime sector. This study investigates risk analysis and mitigation strategies for a Hybrid Energy Storage System (HESS) applied to a 11-meter fully-electric Seabus, configured with Lithium Iron Phosphate (LFP) and Lithium Titanate Oxide (LTO). The Hazard Identification (HAZID) method is employed to systematically identify potential hazards during operation, covering technical, operational, and environmental aspects. The findings reveal that hazards with the highest risk ranking include explosion and battery fire, both of which pose severe threats to vessel safety and environmental integrity. To address these critical risks, appropriate mitigation strategies are proposed, including advanced battery management systems, physical protection of critical components, and emergency operational procedures tailored to maritime safety standards. This research highlights the importance of integrating HAZID into the design and operation of HESS to enhance reliability and safety